Pengaruh Media Interaktif Berbasis Power point Terhadap Hasil Belajar IPS Kelas IV Sekolah Dasar - Roehmatulloh, Dwi Novela; Susilo, Tri Achmad Budi; Maqfiro, Mochammad Ludfy Hadis (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This study aims to improve learning outcomes by using interactive media based on power point. This type of research is a Quasi Experiment Desaign, with the Nonequivalent Pretest-Postest desaign the sample used amounted to 30 students who were divided into 2 classes, namely class IV-A as the experimental class and class IV-B as the control class. The instruments used are pretest-posttest questions and student response questionnaire sheets. There is a difference in the average learning outcomes in the control class of 63.33% and the experimental class of 88.66%. The influence of this media on learning outcomes is proven through several tests, namely validity, reliability, normality and hypothesis testing. The t test results show t (3.567) > t table (2.160) and (0.003) < (0.005) meaning that H0 is rejected and the results of student responses in interactive media get a score of 81% in the very good category. Based on the acquisition of the percentage above the effect of interactive media based on power point provides an increase in social studies learning outcomes grade IV elementary school.